Prevention of aerosol transmission in dental preparation during the corona virus (covid -19) pandemic facing the new normal - Andi Sumidarti (Journal of Dentomaxillofacial Science, 2021)
Objectives: To prepare for the needs of facing the new normal era in dental practice, especially in aerosol transmission for dental conservation treatment.Methods: Literature review method. Literature searches are obtained from several literature study sources related to the topics to be discussed.Results: The spread of COVID-19 infection could be through aerosol transmission generated during dental conservation treatment.Conclusion: Special precautions are considered to be effective during dental care procedures during the COVID-19 pandemic facing the new normal era.